Making the Connection: NEPA Processes for National Environmental Policy - Ted Boling (Washington University Journal of Law & Policy, 2010)
The goals of NEPA‘s sponsors were transformational: to integrate environmental protection and sustainable development considerations into all decisions made regarding federal agency action. NEPA section 102(2) contains action-forcing provisions that provide authority and mandates to translate this transformational policy into action. Part I of this Article reviews NEPA‘s provisions implementing this transformation mandate. Part II evaluates those purposes against the current state of NEPA implementation. Part III concludes with proposals for improving the promotion of actions that (1) prevent or eliminate environmental damage; (2) stimulate health and welfare; and (3) increase understanding of the relationship between personal well-being and ecological systems and natural resources.
Keywords: Environmental policy; Sustainable development; Environmental protection; Environmental impact analysis; National Environmental Policy Act of 1969